Molecular classification of breast cancer: An overview with emphasis on ethnic variations and future perspectives - Mohamed A Shawarby; Dalal M Al-Tamimi; Ayesha Ahmed (Saudi Journal of Medicine and Medical Sciences, 2013)
Morphologically identical breast cancers can display divergent clinical outcomes and responses to therapy. This can predominantly be attributed to molecular class differences that exist amongst histologically similar cancer types. Consequently, molecular classification can be more powerful than histopathology as a predictive factor for the different treatments. This article reviews the molecular classification of breast cancer and emphasizes that ethnic variations may exist in molecular class prevalence patterns. It also highlights key insights into the currently defined molecular classes as provided by ongoing research on primary breast cancers using recent state-of-the-art technology. Such research is revealing that significant molecular heterogeneity may exist within the molecular classes themselves. More diverse ethnic variations may also be unraveled. The results of ongoing and upcoming research may provide more precise prognostic and predictive information about breast cancer and perhaps a breakthrough step toward "personaliziation" of breast cancer treatment. Forty-one relevant articles (2000-2012) extracted through PubMed and Google advanced searches and at our institute′s library were utilized to prepare the article, along with results of published and ongoing research by the authors.